Optimizing the Role of MSMEs in Regional Economic Growth: Challenges and Opportunities - Hasbiah; Teguh Suharyanto; Virda Febriani Putri Irwan; Fika Faridotul; Chasanah (Journal of Economic Education and Entrepreneurship Studies, 2024)
This research aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in boosting the economy of West Papua, with a focus on the challenges and opportunities faced by this sector. Using a mixed-method approach, data were collected through surveys, in-depth interviews, and focus group discussions. The findings indicate that MSMEs in West Papua face several key challenges, including limited access to capital, low financial literacy, and inadequate infrastructure, such as internet and electricity access. Despite these challenges, there are significant opportunities for MSMEs to grow, particularly through the use of digital technology and e-commerce. The study also found that government policy support has not been fully effective in aiding MSME development in this region. Proposed solutions include improving access to capital, enhancing financial literacy, and digitizing business processes to increase MSME competitiveness. This research offers policy recommendations that can be implemented to encourage MSME growth in West Papua, thus contributing more significantly to the national economy.